Factors influencing corporate office relocation A comparison of three Gothenburg business districts - Haraldsson, Alfred; Håkansson, Erik (My University, 2023)
The development of a city requires the creation of appealing alternatives to the central business district (CBD). This thesis aims to explore why office-based companies choose to move from one location to another. Based on a literature review of factors that influence the decision of companies to relocate, 13 interviews with rental brokers, property owners and tenants have been conducted. These interviews have been held with managers from companies located in the Gothenburg CBD and two emerging office districts, Masthuggskajen and Gårda. The interviews provide insights into the decision-making process of companies and the practical challenges and considerations involved in a move. Findings indicate that companies may move for primarily three reasons: employer branding, facility improvements and location. The critical factor in the choice of an office is the location, but the definition of a good location varies depending on the company’s specific needs and values. The pandemic has affected companies´ needs, to prioritize factors such as comfort and services to a higher extent. Thus, the focus on work-life balance is valued among the employees. Furthermore, the study shows that the property owners focus on creating buildings with a “concept” that offers a broad range of services and facilities beyond the traditional office to fulfil the needs of the tenants. Although the companies stated that the cost is a decisive factor when relocating, it is not the most important one. Companies are willing to pay premium rent to get a modern and unique office.
Keywords: CBD alternatives; city development; decision-making process; employer branding; office relocation; remote work; skilled workforce